The history of prestressed concrete: 1888 to 1963 - Dinges, Tyson (Kansas State University, 2009)
The concept of prestressed concrete appeared in 1888 when P.H. Jackson was granted the first patent in the United States for prestressed concrete design. Jackson’s idea was perfect, but the technology of high strength steel that exhibited low relaxation characteristics was not yet available. It was not until Eugene Freyssinet defined the need for these materials that prestressed concrete could be used as a structural building material. Unfortunately, although Freyssinet, a brilliant structural designer and bridge builder, lacked the teaching qualities necessary to communicate his ideas to other engineers. It would take Gustave Magnel to write the first book of design in prestressed concrete, communicating this idea to designers worldwide. Magnel designed and built the legendary Walnut Lane Bridge in Philadelphia, which revolutionized prestressed concrete in America. Simultaneously, Urlich Finsterwalder, the German bridge builder and designer, was revolutionizing the construction means and methods for prestressed concrete bridges. For example, Finsterwalder invented the free-cantilever construction method of prestressed concrete bridges, which allowed long span bridges to be constructed without stabilized shoring. He then designed stress-ribbon bridges, which would eventually allow prestressed concrete to span distances only steel suspension bridges could achieve. However, it wasn’t until Paul Abeles and his peer, H. von Emperger studied and tested prestressed concrete that the idea of “partial prestressing” emerged. Initially, Freyssinet and Magnel were adamant that prestressed concrete should not be allowed to exhibit any tensile forces at sustained loading. Later, the Roebling family developed the first stress--relieved wire followed by the first stress-- relieved strand. T.Y. Lin once again brought prestressed concrete back into the spotlight when he organized the First Prestressed Concrete World Conference in 1957. Shortly after this conference, Lin published a technical paper in the Prestressed Concrete Institute (PCI) Journal that introduced a new Load Balancing technique which allowed most structural engineers to design prestressed concrete very easily.
Keywords: history of prestressed concrete; Engineering, Civil (0543)